2019
DOI: 10.1080/15384047.2019.1617571
|View full text |Cite
|
Sign up to set email alerts
|

LINC00958 regulated miR-627-5p/YBX2 axis to facilitate cell proliferation and migration in oral squamous cell carcinoma

Abstract: Oral squamous cell carcinoma (OSCC), the subtype of head and neck cancers, is notorious for its high incidence and death rate. The role of long non-coding RNAs (lncRNAs) is discovered to be significant for the canceration and cancer progression. Long intergenic non-protein coding RNA 958 (LINC00958) is discovered as a carcinogene in multiple cancers, such as gastric cancer, pancreatic cancer, and glioma, but there has been no report about how LINC00958 functions in OSCC. The objective of our study is to unfold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 27 publications
(37 reference statements)
1
24
0
Order By: Relevance
“…Several studies have suggested that LINC00958 and HOXC13-AS are significantly associated with tumor progression, migration, and invasion. A recent report showed that LINC00958 regulated the miR-627-5p/YBX2 axis and facilitated cell proliferation and migration in oral squamous cell carcinoma (Chen et al, 2019a). Wen et al reported that Figure 6 LINC00958 and HOXC13-AS expression levels in tumors and cells.…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have suggested that LINC00958 and HOXC13-AS are significantly associated with tumor progression, migration, and invasion. A recent report showed that LINC00958 regulated the miR-627-5p/YBX2 axis and facilitated cell proliferation and migration in oral squamous cell carcinoma (Chen et al, 2019a). Wen et al reported that Figure 6 LINC00958 and HOXC13-AS expression levels in tumors and cells.…”
Section: Discussionmentioning
confidence: 94%
“…Long non-coding RNA 00958 (LINC00958) is originally identified as an oncogenic gene in bladder cancer by Seitz et al [8]. Subsequent studies demonstrated that LINC00958 is upregulated in several other malignancies, including glioma [9], oral [10], gastric [11], pancreatic [12], and gynecological cancer [13,14]. The involvement of LINC00958 in HCC has not yet been documented, prompting us to explore its biological functions and clinical value.…”
Section: Introductionmentioning
confidence: 99%
“…The abnormally high expression of LINC00958 has been demonstrated in patients with gastric cancer, and was found to be associated with metastasis and unfavorable prognosis (15). Additionally, evidence indicates that LINC00958 accelerates the progression of oral squamous cell carcinoma and pancreatic cancer by acting as a microRNA (miR/miRNA) sponge (16,17). However, to the best of our knowledge, the function of LINC00958 in CRC has not yet been studied, which has peaked our interest.…”
Section: Introductionmentioning
confidence: 99%